2013
DOI: 10.4103/2229-5119.110351
|View full text |Cite
|
Sign up to set email alerts
|

Anti-anemic potential estimation on mice and characterization of flavonoids using high performance thin layer chromatography in Wrightia tinctoria bark fraction

Abstract: Objective: Wrightia tinctoria commonly known as "Mitha indrajao" (family Apocynaceae) has reported to have wound healing, immunomodulatory, anti-infl ammatory, anti-oxidant, and anabolic effects. This study was aimed to explore anti-anemic activity of W. tinctoria focusing fl avonoids as anti-oxidant phyto-constituents. Materials and Methods: Flavonoid fraction of W. tinctoria bark methanolic extract (FWT) was separated, quantitative polyphenol estimation, and qualitative identifi cation was performed. LD 50 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
(17 reference statements)
1
11
0
Order By: Relevance
“…Our data showed that VO contained higher amounts of polyphenols than WT, which was more than previously reported values (TPC—35.4 mg/g and TFC—22.8 mg/g; Ebrahimzadeh et al, ). However, TPC of WT is greater than the values reported by Jain, Goyal, and Ramawat (; 19.5 mg/g), in accordance with Bigoniya, Singh, Singh, and Shukla (; 30.46 mg/g), and lower than Ramalakshmi et al (; 55. mg/g). Additionally, TFC and PC followed a trend similar to that of total polyphenols.…”
Section: Resultssupporting
confidence: 68%
“…Our data showed that VO contained higher amounts of polyphenols than WT, which was more than previously reported values (TPC—35.4 mg/g and TFC—22.8 mg/g; Ebrahimzadeh et al, ). However, TPC of WT is greater than the values reported by Jain, Goyal, and Ramawat (; 19.5 mg/g), in accordance with Bigoniya, Singh, Singh, and Shukla (; 30.46 mg/g), and lower than Ramalakshmi et al (; 55. mg/g). Additionally, TFC and PC followed a trend similar to that of total polyphenols.…”
Section: Resultssupporting
confidence: 68%
“…[20] Methanolic extract of W. tinctoria bark with rich flavonoid content has potential antianemic and hematopoietic effect. [14] Kedar and Chakrabarti have reported that the cholesterol, TG and SGPT levels are increased in case hyperglycemia. Deficiency of insulin caused the increase in the level of these enzymes in liver and serum of diabetic animals.…”
Section: Discussionmentioning
confidence: 99%
“…[12] The methanolic, ethanolic and ethyl acetate extract of W. tinctoria showed rich presence of alkaloid, glycoside, triterpene, tannins and phenolic compounds. [13,14] Until date, no pharmacological evidence for effectiveness of W. tinctoria phenolic and flavonoid content has been reported. Flavonoids contain wide range of biological activity and lot of research has been carried out on their potential role in treating diabetes and other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the RBC tests showed no difference in the number of RBCs between the treatment and control groups, which means the CGEE did not affect erythropoiesis or the osmotic pressure on erythrocyte cells [14]. Some bioactive substances in a plant can induce anemia, which is characterized by low RBC and Hb levels [15,16]. The administration of 5000 mg/kg BW CGEE was not able to induce anemia during treatment.…”
Section: Discussionmentioning
confidence: 99%